Evaluasi Asesmen Nasional (AN) di Sekolah Menegah Atas di Medan - Kamila Harahap; Fathul Mulki Nasution; Irsan Rangkuti; Joharis Lubis (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
The transformation of Indonesia’s educational evaluation system from the National Examination (UN) to the National Assessment (AN) is intended to improve education quality through a more comprehensive approach. This study examines the implementation of the National Assessment at SMA Negeri 21 Medan, with a focus on the disparity between the theoretical framework of formative assessment and its practical execution in the field. The research utilizes the discrepancy evaluation model with a qualitative methodology. Data were gathered through in-depth interviews, focus group discussions (FGD), participatory observations, and document analysis.The findings reveal that although the National Assessment is designed as a formative evaluation, in practice, it is still regarded as a summative assessment disconnected from the learning process. The execution of the Minimum Competency Assessment (AKM) continues to be dominated by multiple-choice questions, restricting the comprehensive evaluation of competencies. Moreover, the use of assessment results for educational enhancement remains suboptimal due to reporting delays and the insufficiently diagnostic format of the reports. Key supporting factors for implementation include strong school leadership, adequate infrastructure, and collaboration among schools. However, several obstacles persist, such as a limited conceptual grasp, inadequate teacher training, and administrative and curricular constraints. This study suggests reinforcing teachers’ conceptual understanding, enhancing the feedback system for assessment outcomes, and fostering deeper integration of formative assessment principles into school learning strategies. By doing so, the National Assessment can be more effectively leveraged to improve the quality of education in Indonesia.